On the Streets, Under Arrest: Policing Homelessness in the 21st Century. Issue 11 (28th October 2015) - Stuart, Forrest
Abstract: Since the earliest days of the discipline, sociologists have viewed homelessness as a premier index of inequality and poverty more generally. Sociologists have increasingly turned to the regulation and policing of homelessness as a lens for analyzing how a given society understands and interacts with those who exist at the bottom of the social hierarchy. Against this intellectual backdrop, this article traces recent developments in the policing of homelessness, as well as the corresponding academic attempts to make sense of this empirical phenomenon. Doing so demonstrates that a vast majority of analyses have focused narrowly on the punitive and exclusionary functions of policing and, as a result, have tended to overlook issues surrounding differentiated functions, organizational dynamics, spatial contingencies, and questions of agency. This article complicates existing approaches and thereby lays the foundation for a more accurate and nuanced rendering of the policing of homelessness.